Detection of discontinuities in water-air two-phase flow using ultrasonic flow detection - Synowiec, Piotr; Wędrychowicz, Wiesław; Wróblewska, Elżbieta; Andruszkiewicz, Artur; Piechota, Piotr; Betkier, Grzegorz (Instal, 2025)
The article focuses on the application of ultrasonic flow detection for identifying discontinuities in water-air two-phase flow. It details the measurement principle and the methodology for testing the measurement system. The paper then presents exemplary research results for horizontal flow regimes: bubbly flow and slug flow.This method enables the determination of several key parameters characteristic of two-phase flow, specifically: gas phase distribution, slug height and length, and gas phase velocity. Furthermore, the void fraction of the gas phase in the flow can also be determined. By utilizing multiple ultrasonic sensors mounted in a single measurement plane, an ultrasonic tomography system can be constructed.
Keywords: ultrasonic flow detection; flow measurement; two-phase flow; measurement uncertainty